At the Borders of Public and Private: The Oturmalar of Kayseri - Kurtuluş, Cengiz; Küçükural, Önder; Shkreli, Etrit (Middle East Institute, 2015)
This article examines the political implications of the vibrant social life of the city of Kayseri in Turkey. By using qualitative data collected by participant observations and in-depth interviews, we discuss the traditional form of gatherings called oturmalar. We evaluate the lively participation in public gatherings whose borders blur public, private, and religious fields in the light of more theoretical debates on the public sphere and situated within the literature on the public sphere in the Middle East.
FSM Vakıf Üniversitesi, Medeniyetler İttifakı Enstitüsü